Pemetaan lanskap global penelitian ketahanan mental: Tren, kontribusi, dan tema kunci (2014-2024) - Noor Akhmad; Maulidin Maulidin; Fadli Zainuddin (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2025)
This study aims to analyze trends, contributions, and key themes in mental toughness research using a bibliometric approach. Data were retrieved from Scopus with the search query TITLE-ABS-KEY ("mental toughness" AND (athlete OR sport)) for the period 2014-2024, focusing on English-language journal articles. A total of 311 documents were analyzed using Bibliometrix R-Package, Biblioshiny, and VOSviewer software to map collaboration networks, geographical distribution, and dominant research themes. The main findings of this study show that developed countries, particularly the United Kingdom, the United States, and Australia, contribute the majority of global publications. Meanwhile, Asian countries such as China, Malaysia, and Indonesia demonstrate significant growth and considerable potential in this region. Thematically, mental toughness remains the core theme of the research, with key subthemes such as motivation, resilience, and athletic performance being highly dominant. Publication trends show significant growth, with the number of documents increasing from 2014 to 2024. These findings provide important insights into the global dynamics of mental toughness research and emphasize the importance of integrating quantitative and qualitative approaches. This study opens opportunities for further development in the fields of sports psychology, education, and mental toughness.